2018
DOI: 10.15359/mhs.14-2.4
|View full text |Cite
|
Sign up to set email alerts
|

Determinación De La Actividad Física en El Recreo Escolar: Combinando Mediciones De Actividad Física Y La Perspectiva Estudiantil

Abstract: Esta obra está bajo una Licencia Creative Commons Atribución-NoComercial-SinDerivar 3.0 Internacional.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 27 publications
0
5
0
2
Order By: Relevance
“…From a causal standpoint, the most effective learning occurs when learners have positive emotions, are engaged in the class, and are not stressed. Research establishes that information is more likely to be fixed in long-term memory when it is relevant to the learner (3) .…”
Section: Affectivity As Cause and Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…From a causal standpoint, the most effective learning occurs when learners have positive emotions, are engaged in the class, and are not stressed. Research establishes that information is more likely to be fixed in long-term memory when it is relevant to the learner (3) .…”
Section: Affectivity As Cause and Effectmentioning
confidence: 99%
“…Another factor that conditions the quality of life is the social and cultural norms concerning physical activity, including the built environment in cities; these environments typically restrict physical activity possibilities (1) . Indeed, a study by Álvarez et al (3) , concluded that people's perception is that the environments, due to environmental barriers, do not favor the practice of physical activity. Besides, avoiding low energy-cost activities, such as spending a long time sitting, should be recommended for the population's physical activity guidelines (4) .…”
Section: Introductionmentioning
confidence: 99%
“…En respuesta del sedentarismo en la niñez costarricense se ha considerado al entorno escolar como el lugar que reúne las mayores características para poder incidir sobre la problemática mencionada, no solo porque es el entorno en la vida de la niñez donde conviven la mayor cantidad de tiempo, sino también, porque ofrece el mayor potencial para ser modificado y obtener una niñez más activa (Álvarez, et al 2018;Chaves, 2013;Sallis et al, 2012).…”
Section: Influencia Del Entorno Escolar En La Práctica De La Actividaunclassified
“…Since children spend most of their time at school, this context presents a great opportunity for improvement and to increasephysical activity [15]. Opportunities for physical activity at school ariseduring the physical education session [20,21], through the teaching of other curricular contents [15,22], and during the breaks that occur during the school day [9,23,24,25].…”
Section: Introductionmentioning
confidence: 99%